2009
DOI: 10.3324/haematol.13206
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo expansion of hematopoietic progenitor cells is associated with downregulation of  4 integrin- and CXCR4-mediated engraftment in NOD/SCID  2-microglobulin-null mice

Abstract: BackgroundSeveral studies indicate that ex vivo cytokine-supported expansion induces defective hematopoietic stem cell engraftment. We investigated the role of α4 integrin, α5 integrin and CXCR4 in engraftment of unmanipulated and cytokine-treated human cord blood CD34 + cells. Design and MethodsUncultured or expanded CD34 + cells were infused in NOD/SCID-β2microglobulin-null mice. The function of α4, and α5 integrins and CXCR4 was assessed by incubating cells with specific neutralizing antibodies, prior to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…3.1 VCAM-1-dependent migration was enhanced in expanded HSC co-cultured with MSC It has been shown that short-term HSC expansion using early-acting cytokines, such as SCF, TPO and Flt3L, reduced HSC in vitro ability to migrate in VCAM-1-covered inserts [5,7]. This finding has been correlated with reduced in vivo HSC homing and engraftment [6,7].…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…3.1 VCAM-1-dependent migration was enhanced in expanded HSC co-cultured with MSC It has been shown that short-term HSC expansion using early-acting cytokines, such as SCF, TPO and Flt3L, reduced HSC in vitro ability to migrate in VCAM-1-covered inserts [5,7]. This finding has been correlated with reduced in vivo HSC homing and engraftment [6,7].…”
Section: Resultsmentioning
confidence: 89%
“…This finding has been correlated with reduced in vivo HSC homing and engraftment [6,7]. We first assessed whether short-term HSC expansion with SCF, TPO and Flt3L in the presence of MSC would improve HSC migration, since ex vivo HSC co-culturing with MSC led to enhanced HSC engraftment [13,15,16].…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…11 Inactivation of CXCR4 by neutralizing antibodies has been shown to impair stem/progenitor cell engraftment in the bone marrow. 12 Accumulating evidence indicates that the level of CXCR4 surface expression on BMCs determines the efficiency of homing and the subsequent angiogenic response of target tissues. 13, 14 Over-expression of CXCR4 in mesenchymal stem cells (MSCs) or CD34+ cells enhances the migration of these cells towards SDF-1 in vitro 15 and increases the efficiency of bone marrow transplant in vivo 16 .…”
Section: Introductionmentioning
confidence: 99%